The protective effects of caffeine and melatonin on antioxidant enzymes in rat fetal lung tissues - Nisari, Mustafa; Yılmaz, Seher; Göçmen, Ayşe Yeşim; Karataş, Ersin; Al, Özge (Journal of Surgery and Medicine, 2019)
Aim: Teratogenic substances such as nicotine, alcohol, caffeine, and derivatives, which pregnant women may get exposed to unconsciously or use consciously can harm the mother and directly or indirectly damage embryonal and fetal tissues. Melatonin has been shown to exert direct free radical trapping and indirect antioxidant effects in different organs and tissues. In this study, we aimed to biochemically evaluate the effects of melatonin, a powerful antioxidant battling the oxidative effects of high and low doses of caffeine administered to pregnant rats in fetal lung tissues. Methods: In our study, 35 pregnant adult female Sprague-Dawley rats were used. Pregnant rats were divided into 7 groups with 5 rats in each. Caffeine and melatonin were administered for 20 days during the pregnancy. The gestational period lasted 21 days in average. The offspring were sacrificed, and lung tissues were removed. Superoxide dismutase (SOD), glutathione (GSH), glutathione disulfide (GSSG), total oxidant status (TOS), total antioxidant status (TAS), calcium (Ca) and vitamin D (Vit D) were measured by spectrophotometric assay. The oxidative stress index (OSI) and total glutathione (GSH/GSSG) were determinants of oxidative stress and were calculated as TOS/TAS and GSH/GSSG ratios, respectively. Results: The highest TAS value was obtained in the Melatonin group (M) group. GSH and GSH/GSSG was highest in the control group, whereas GSSG was the highest in the high-dose caffeine group (HDC) group. HDC group had the highest SOD value compared to the other groups (P<0.05). Conclusions: According to these data, it was determined that caffeine used during pregnancy delayed the development of lung, and melatonin, which is a strong antioxidant, minimized the delay.